Human Resource Competencies, Internal Control Systems, Accounting Information Systems And Quality Of Financial Reports - Sulis Hidayatul Iska (Citakonsultindo, 2024)
Previous research or relevant research is very important in research or scientific articles. Previous research or relevant research functions to strengthen theories and phenomena of the relationship or influence between variables. This article reviews the factors that influence the quality of financial reports, namely: human resource competency, internal control systems, and the application of accounting information systems through a literature study. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: human resource competency influences the quality of financial reports; the internal control system influences the quality of financial reports; and the application of accounting information systems influences the quality of financial reports. This research shows that improvements in these three aspects synergistically contribute to improving the quality of financial reports, which ultimately supports the success and sustainability of the company.